STRUKTUR MODAL DAN PROFITABILITAS PERUSAHAAN ANGGOTA HOLDING PT PUPUK INDONESIA (PERSERO) - Rahmat Setiawan; Koko Sudiro (Jurusan Ilmu Ekonomi Prodi Ekonomi Pembangunan Fakultas Bisnis dan Ekonomika Universitas Surabaya, 2018)
This research aims to investigate the effect of capital structure on profitability of the firms included in holding company PT Pupuk Indonesia (Persero). Capital structure is measured by 3 proxies, including Debt to Assets Ratio (DAR), Short-term Loan to Total Assets, and Long-term Loan to Total Assets. Profitability is measured by Return on Assets (ROA). Data were obtained from financial reports quarterly during period 2011-2015. The research results show that both DAR and Short-term Loan to Total Assets have negative significant effects on profitability. Long-term Loan to Total Assets does not have a significant effect on profitability.